2022
DOI: 10.1007/s11104-022-05591-2
|View full text |Cite
|
Sign up to set email alerts
|

Digging deeper: microbial communities in subsoil are strongly promoted by trees in temperate agroforestry systems

Abstract: Aims Temperate alley-cropping agroforestry systems maintain agricultural production while offering several environmental benefits. Central benefits of agroforestry systems such as the ‘safety-net’-role of the trees for leached nutrients are mainly due to processes occurring below the soil surface: the subsoil. Microorganisms in the subsoil may play a key role in the ‘safety-net’-function as they can improve the capturing and uptake of nutrients by the trees. Systematic investigations of microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…Therefore, even though dispersal limitation is important in the assembly of deep soil microbial communities, the key role of deterministic processes driven by potential biological interactions (e.g., plant–fungi and bacteria‐fungi associations) in deep soil microbial assembly cannot be ignored. Deterministic processes dominated by fungi and constant presence of arbuscular mycorrhizal and dominant determinism for fungal assembly down to deep depth in the present study also confirmed this point (Figure 1b and Figures S7 and S10), as arbuscular mycorrhizal is a representative of the direct association between fungi and plant roots (Beule et al., 2022; Carteron et al., 2021; Lozano et al., 2021). By comparison, a susceptible environment between sampling locations in topsoil would create more diverse environmental heterogeneity that shapes the microbiome and enhances the influence of environmental factors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, even though dispersal limitation is important in the assembly of deep soil microbial communities, the key role of deterministic processes driven by potential biological interactions (e.g., plant–fungi and bacteria‐fungi associations) in deep soil microbial assembly cannot be ignored. Deterministic processes dominated by fungi and constant presence of arbuscular mycorrhizal and dominant determinism for fungal assembly down to deep depth in the present study also confirmed this point (Figure 1b and Figures S7 and S10), as arbuscular mycorrhizal is a representative of the direct association between fungi and plant roots (Beule et al., 2022; Carteron et al., 2021; Lozano et al., 2021). By comparison, a susceptible environment between sampling locations in topsoil would create more diverse environmental heterogeneity that shapes the microbiome and enhances the influence of environmental factors.…”
Section: Discussionsupporting
confidence: 85%
“…of arbuscular mycorrhizal and dominant determinism for fungal assembly down to deep depth in the present study also confirmed this point (Figure 1b and Figures S7 and S10), as arbuscular mycorrhizal is a representative of the direct association between fungi and plant roots (Beule et al, 2022;Carteron et al, 2021;Lozano et al, 2021). By comparison, a susceptible environment between sampling locations in topsoil would create more diverse environmental heterogeneity that shapes the microbiome and enhances the influence of environmental factors.…”
Section: Deterministic Processes Dominated By Fungi and Constant Pres...supporting
confidence: 85%
“…The depth of soil sampling is significantly affected abundance and diversity of microbial community ( Böer et al, 2009 ; Mendes and Tsai, 2014 ; Fu et al, 2023 ). The selection of the 0–10 cm depth range for collecting sediment samples is often based on the findings of earlier researchers ( Zhao et al, 2021 ; Beule et al, 2022 ). Randomly collected samples were mixed to get one composite sample from each site, Site-1, and Site-2, and were designated as PPS-1 and PPS-2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Deep subsoil microbiota close to the roots is crucial for agricultural soil system functioning (Ryan et al, 2023) and nutrient cycling (Beule et al, 2022;Naylor et al, 2022;Naylor et al, 2023), especially in agricultural production systems during drought, low nutrient supply, and extensive agriculture practices. Most root microbiome studies are conducted at the plow horizon (0-30 cm), where most roots are located (Maeght et al, 2013;Simonin et al, 2020;Jaiswal et al, 2022;Naylor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%